Developing a comprehensive shipment policy through modified epq model considering process imperfections, transportation cost, and backorders - Waseem Sajjad; Misbah Ullah; Razaullah Khan; Mubashir Hayat (Logistics, 2022)
Background: Determining the optimum shipment quantity in a traditional production system is a competitive business dimension, and developing a reliable shipment policy is decisive for long-term objectives. Currently, significant research in this domain has mainly focused on the optimum shipment lot sizing in a perfect production system without considering the imperfections in the production processes and logistics. It has been well established that the real production inventory system acts as an imperfection in the overall production management loop. Methods: This research deals with designing a new shipment policy considering the imperfections in the production processes and undertaking some influential factors, such as the transportation cost, the actual production inventory, defective items, and backorders. Results: In the developed mathematical framework, the lot-sizing problems, imperfections in the production processes, retailers, and distributors are considered with equal-sized shipment policy to attain pragmatic and real-time results. Conclusions: The developed framework considers an all-unit-discount transportation cost structure. The numerical computations, as well as sensitivity analysis, are performed to point out the specifications and validation of the proposed model.
Keywords: 650; backorders; economic production quantity; imperfection in the process; production management; supply chain management; transportations costs